Penggunaan PXE (Preboot Execution Environment) untuk Mengontrol Pemilihan Operating System Saat Booting - Christian Adi Widjaja; Henry Novianus Palit; Agustinus Noertjahyana (Jurnal Infra, 2016)
One of the Informatic laboratories in Petra Christian University is Multimedia laboratory. In this laboratory, every computer has multiple operating systems. Lot of class activities use Windows operating systems and outside class activities users usually use Ubuntu operating system. Changing the operating system from Windows 7 to Ubuntu takes a long time because the operating system must be changed manually. Changing the operating system manually may not cause a problem if the change is just applied to a single computer. If the number of computers is 20, further more, the operating system is changed 2 – 4 times a day, then changing the operating system may take a lot of time. This will trouble the lab assistant too much and delay the class activities.